2019
DOI: 10.1111/desc.12857
|View full text |Cite
|
Sign up to set email alerts
|

Brain activity patterns of phonemic representations are atypical in beginning readers with family risk for dyslexia

Abstract: There is an ongoing debate whether phonological deficits in dyslexics should be attributed to (a) less specified representations of speech sounds, like suggested by studies in young children with a familial risk for dyslexia, or (b) to an impaired access to these phonemic representations, as suggested by studies in adults with dyslexia. These conflicting findings are rooted in between study differences in sample characteristics and/or testing techniques. The current study uses the same multivariate functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 94 publications
(130 reference statements)
3
24
1
Order By: Relevance
“…In our data, only French poor readers had a significantly lower activation relative to their controls at this location, but in both languages, poor readers exhibited an unstable activation pattern across fMRI runs, suggesting fragile phonetic representations evoked by written stimuli. In agreement with this interpretation, Vandermosten et al, 2020 also observed disrupted phonological representation in a multivariate pattern analysis but not in the univariate activation analysis in beginning readers with a family risk for dyslexia. Again, because this site is also under-activated during spoken language processing in illiterates and in preliterate children compared to adult and children readers ( Dehaene et al, 2010 ) we cannot ascertain whether its anomalous activation is a cause or a consequence of the reading disability.…”
Section: Discussionsupporting
confidence: 69%
“…In our data, only French poor readers had a significantly lower activation relative to their controls at this location, but in both languages, poor readers exhibited an unstable activation pattern across fMRI runs, suggesting fragile phonetic representations evoked by written stimuli. In agreement with this interpretation, Vandermosten et al, 2020 also observed disrupted phonological representation in a multivariate pattern analysis but not in the univariate activation analysis in beginning readers with a family risk for dyslexia. Again, because this site is also under-activated during spoken language processing in illiterates and in preliterate children compared to adult and children readers ( Dehaene et al, 2010 ) we cannot ascertain whether its anomalous activation is a cause or a consequence of the reading disability.…”
Section: Discussionsupporting
confidence: 69%
“…The left superior temporal gyrus is a region that is reliably engaged during auditory phonological awareness tasks (e.g. Boets et al, 2013 ; Leonard and Chang, 2014 ; Weiss et al, 2018 ; Vandermosten et al, 2020 ; Wang et al, 2020 ). Therefore, it is possible that 7- to 8-year-old children rely more on their refined phonological representations in the left superior temporal gyrus to solve small grain size problems.…”
Section: Discussionmentioning
confidence: 99%
“…Neural alterations in this region have previously been associated with dyslexia (e.g., Peterson & Pennington, ; Richlan et al, ; Shaywitz & Shaywitz, ) as well as familial risk (e.g., Im et al, ; Raschle et al, , ; Raschle et al, ). Recent effort has been made to disentangle these two effects by comparing FHD+ good and/or poor readers with controls (Hakvoort, van der Leij, Maurits, Maassen, & van Zuijen, ; Vanderauwera, Wouters, Vandermosten, & Ghesquière, ; Vandermosten et al, ). Atypical brain responses for speech and phonological processing were observed in bilateral superior temporal regions in both good and poor readers with a family history when compared to controls, indicating an effect of familial risk (Vandermosten et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, a small group of FHD+Impaired children ( n = 12) were included in the current analyses, limiting the result generalizability. However, it should be noted that the primary analyses have been devoted to characterizing the atypical neural mechanisms underlying reading development in FHD+Typical compared to FHD−Typical children ( n = 60), which few studies have investigated (however, see Vandermosten et al, ). Future studies with a large sample are needed to determine the exact developmental timelines of compensatory/protective mechanisms that support literacy acquisition in FHD+ children.…”
Section: Discussionmentioning
confidence: 99%